2022
DOI: 10.1111/apt.17101
|View full text |Cite
|
Sign up to set email alerts
|

Chicago classification v4.0 protocol improves specificity and accuracy of diagnosis of oesophagogastric junction outflow obstruction

Abstract: Summary Background Chicago classification version 4.0 (CCv4.0) introduced stringent diagnostic criteria for oesophagogastric junction outflow obstruction (EGJOO), in order to increase the clinical relevance of the diagnosis, although this has not yet been demonstrated. Aims To determine the prevalence of EGJOO using CCv4.0 criteria in patients with CCv3.0‐based EGJOO, and to assess if provocative manoeuvres can predict a conclusive CCv4.0 diagnosis of EGJOO. Methods Clinical presentation, high resolution manom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…They also demonstrated that a higher median rapid drink challenge (RDC)-IRP, specifically 16.7 mmHg, is predictive of conclusive EGJOO by CCv4.0 criteria. 10 These data highlight the many ways that the updated HRM protocol and definition of EGJOO are a large leap forward in minimising 'false alarms' (Figure 1). Importantly, these updates in CCv4.0 promote a higher level of rigour and confidence in the manometric…”
Section: Editorial: Reducing False Alarms With Oesophagogastric Junct...mentioning
confidence: 94%
See 3 more Smart Citations
“…They also demonstrated that a higher median rapid drink challenge (RDC)-IRP, specifically 16.7 mmHg, is predictive of conclusive EGJOO by CCv4.0 criteria. 10 These data highlight the many ways that the updated HRM protocol and definition of EGJOO are a large leap forward in minimising 'false alarms' (Figure 1). Importantly, these updates in CCv4.0 promote a higher level of rigour and confidence in the manometric…”
Section: Editorial: Reducing False Alarms With Oesophagogastric Junct...mentioning
confidence: 94%
“…4 Visaggi et al examined the impact of these new diagnostic requisites on the prevalence of EGJOO. 10 They identified that CCv4.0 diagnostic criteria (HRM metrics with the addtion of obstructive symptoms and supportive TBE findings) yield higher specificity for EGJOO with an impressive six-fold reduction (from 7.2% to 1.2%) of EGJOO prevalence. Further, they identified a lack of abnormal TBE in those without obstructive symptoms, justifying the requirement for obstructive symptoms for EGJOO in CCv4.0.…”
Section: Editorial: Reducing False Alarms With Oesophagogastric Junct...mentioning
confidence: 98%
See 2 more Smart Citations
“…A standard HRM protocol requires at least ten 5 mL water swallows, obtained in both supine and sitting position. Provocative tests (i.e., multiple rapid swallows—MRS and rapid drinking challenge—RDC) were included to investigate the peristaltic reserve and outflow obstruction [ 38 , 39 ]. According to CCv4.0, the esophagogastric junction (EGJ) morphology and LES relaxation should be assessed first.…”
Section: Introductionmentioning
confidence: 99%